A revision of Panscopaeus (Coleoptera: Staphylinidae: Paederinae). - Assing, Volker (Contributions to Entomology = Beiträge zur Entomologie, 2011)
Based on a revision of types and additional material, seven species of Panscopaeus Sharp, 1889 are recognized: P. lithocharoides (Sharp, 1874), P. yakushimanus (Ito, 1992), P. formosanus sp. n. (Taiwan), P. andrewesi (Cameron, 1931), comb. n. (ex Medon), P. breviusculus (Kraatz, 1859), comb. n. (ex Medon), P. stilicinus (Cameron, 1931), comb. n. (ex Medon), and P. cameroni (Scheerpeltz, 1933), comb. n. (ex Medon). The genus and all its species are (re-)described and illustrated. Panscopaeus is moved from the subtribe Medonina to the Stilicina; its known distribution is confined to the Oriental and southern East Palaearctic regions. The following synonymies are established: Panscopaeus Sharp, 1889 = Medostilicus Coiffait, 1982, syn. n.; Panscopaeus lithocharoides (Sharp, 1874) = Medostilicus deharvengi Coiffait, 1982, syn. n. Lectotypes are designated for Scopaeus lithocharoides Sharp, 1874, Medon andrewesi Cameron, 1931, Lithocharis breviuscula Kraatz, 1859, and Stilicus lithocharoides Cameron, 1924. Additional records, including several new country records, are reported. A key to species is provided. Keywords Coleoptera, Staphylinidae, Paederinae, Stilicina, Medonina, Panscopaeus, Palaearctic region, Oriental region, taxonomy, new species, new synonymies, new combinations, lectotype designations, key to species, additional records. Nomenclatural Acts deharvengi Coiffait, 1982 (Medostilicus), syn.nov. of Panscopaeus lithocharoides (Sharp, 1874) andrewesi (Cameron, 1931) (Panscopaeus), LT; comb.nov. hitherto Medon andrewesi Cameron, 1931 breviusculus (Kraatz, 1859) (Panscopaeus), LT; comb.nov. hitherto Lithocharis breviuscula Kraatz, 1859 cameroni (Scheerpeltz, 1933) (Panscopaeus), comb.nov. hitherto Medon cameroni Scheerpeltz, 1933 formosanus Assing, 2011 (Panscopaeus), sp. n. lithocharoides (Sharp, 1874) (Panscopaeus), LT described as Scopaeus lithocharoides stilicinus (Cameron, 1931) (Panscopaeus), LT; comb.nov. hitherto Medon stilicinus Cameron, 1931